2014
DOI: 10.1002/cne.23589
|View full text |Cite
|
Sign up to set email alerts
|

Neural organization of the second optic neuropil, the medulla, in the highly visual semiterrestrial crab Neohelice granulata

Abstract: Crustaceans are widely distributed and inhabit very different niches. Many of them are highly visual animals. Nevertheless, the neural composition of crustacean optic neuropils deeper than the lamina is mostly unknown. In particular, semiterrestrial crabs possess a highly developed visual system and display conspicuous visually guided behaviors. A previous study shows that the first optic neuropil, the lamina of the crab Neohelice granulata, possesses a surprisingly high number of elements in each cartridge. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 44 publications
(96 reference statements)
3
30
0
Order By: Relevance
“…These terminals appear larger than the tangential terminals identified in the hemispheral parts of the medulla. Sztarker et al (2005Sztarker et al ( , 2014 found transmedullary (Tm) cells in their longitudinal sections with prominent flattened Y-shaped bifurcations in their distal dendrites (Fig. 6.3.5).…”
Section: Termination Patternsmentioning
confidence: 97%
See 4 more Smart Citations
“…These terminals appear larger than the tangential terminals identified in the hemispheral parts of the medulla. Sztarker et al (2005Sztarker et al ( , 2014 found transmedullary (Tm) cells in their longitudinal sections with prominent flattened Y-shaped bifurcations in their distal dendrites (Fig. 6.3.5).…”
Section: Termination Patternsmentioning
confidence: 97%
“…Some of the terminal identities have therefore been assumed based on similarities between these and the termination pattern of the crab (Sztarker and Tomsic, 2014). Terminals that have been identified is the M2 terminal with its radial arborisations and terminals of monopolar cell 3 (M3) and 4 (M4) was with some variations identified as M3' ad M4' according to the naming schedule in Sztarker et al (2014).…”
Section: Termination Patternsmentioning
confidence: 99%
See 3 more Smart Citations